2014
DOI: 10.1038/emm.2013.159
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein mutations in Korean patients with Diamond-Blackfan anemia

Abstract: Diamond-Blackfan anemia (DBA) is a congenital bone marrow failure syndrome characterized by hypoproliferative anemia, associated physical malformations and a predisposition to cancer. DBA has been associated with mutations and deletions in the large and small ribosomal protein genes, and genetic aberrations have been detected in ∼50–60% of patients. In this study, nine Korean DBA patients were screened for mutations in eight known DBA genes (RPS19, RPS24, RPS17, RPS10, RPS26, RPL35A, RPL5 and RPL11) using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Table S1). Thirteen of the VUS have already been found to be pathogenic by published functional studies (Angelini et al., ; Badhai et al., ; Chatr‐Aryamontri et al., ; Chae et al., ; Choesmel et al., ; Cmejlova et al., ; Da Costa et al., ; Gazda et al., ; Hamaguchi et al., ; Idol et al., ;) (Supp. Table S1) and so were not tested in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S1). Thirteen of the VUS have already been found to be pathogenic by published functional studies (Angelini et al., ; Badhai et al., ; Chatr‐Aryamontri et al., ; Chae et al., ; Choesmel et al., ; Cmejlova et al., ; Da Costa et al., ; Gazda et al., ; Hamaguchi et al., ; Idol et al., ;) (Supp. Table S1) and so were not tested in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The DBA database (Boria et al., , ) included 129 RPS19 mutations in 219 patients at its last update in 2010. We reviewed the literature to collect additional RPS19 mutations identified more recently and now have a total of 165 different RPS19 mutations reported in 313 DBA patients (Arbiv et al., ; Chae et al., ; Da Costa et al., ; Delaporta et al., ; Errichiello et al., ; Farrar et al., ; Gerrard et al., ; Ichimura et al., ; Konno et al., ; Kuramitsu et al., ; Landowski et al., ; Ozono et al., ; Pospisilova et al., ; Quarello et al., ; Smetanina et al., ; Solomon et al., ; Tsangaris et al., ; van Dooijeweert et al., ; Wang et al., ; Zhang et al., ). For our study, we selected only those variants for which there was no strong evidence of pathogenicity according to the genetic criteria outlined in Materials and Methods, and obtained 47 VUS reported in 122 patients (39% of RPS19‐mutated patients, approximately 10% of all DBA patients).…”
Section: Resultsmentioning
confidence: 99%
“…Haploinsufficiency of RPs results in ribosome stress and activation of the TP53 tumor suppressor pathway, which is thought to be the main cause of clinical manifestations27). Decreased RPS19 mRNA expression and p53 overexpression were also seen in Korean DBA patients, supporting the idea that haploinsufficiency and p53 overactivation are the central pathways underlying the pathogenesis of DBA26).…”
Section: Diamond-blackfan Anemiamentioning
confidence: 86%
“…Mutations in RPL5 , RPL11 , and RPS17 were also detected 25) . A recent study investigated the genetic abnormalities in nine Korean DBA patients and noted that seven distinct mutations, including three novel mutations, were identified in three RP genes, RPS19 (4/7), RPS26 (2/7), and RPS17 (1/7) 26) . Haploinsufficiency of RPs results in ribosome stress and activation of the TP53 tumor suppressor pathway, which is thought to be the main cause of clinical manifestations 27) .…”
Section: Diamond-blackfan Anemiamentioning
confidence: 99%
“…Interest in Rps26 was aroused recently due to its possible involvement in the pathogenesis of Diamond-Blackfan anemia, an inherited human bone marrow failure syndrome, characterized by the development of anemia during childhood ( 12 ). Indeed, numerous studies demonstrated that mutations in several genes encoding ribosomal proteins, including RPS26a/b , might be linked to Diamond-Blackfan anemia ( 13 15 ). In addition, Rps26 was shown to participate in a variety of cellular processes not directly associated with translation, such as p53 activity, endoplasmic reticulum (ER) stress, the NEDD8 pathway, nonsense-mediated mRNA decay, and filamentous growth ( 2 , 11 , 16 18 ).…”
Section: Introductionmentioning
confidence: 99%